Reva N. S. The status of optional verbal compositional blocks in magazine cosmetics advertisements (in terms of English media discourse) - Reva N. S. (Philological Treatises, 2020)
This article deals with optional compositional-semantic blocks of the magazine advertisements in terms of English media discourse. The types of the blocks in question are being classified; their polyfunctionality and compositional peculiarities in ad texts are being analyzed.